Time interval between diagnostic excision-biopsy of a primary melanoma and sentinel node biopsy: effects on the sentinel node positivity rate and survival outcomes. (May 2022) - El Sharouni, Mary-Ann; Scolyer, Richard A.; van Gils, Carla H.; Ch'ng, Sydney; Nieweg, Omgo E.; Pennington, Thomas E.; Saw, Robyn P.M.; Shannon, Kerwin; Spillane, Andrew; Stretch, Jonathan; Witkamp, Arjen J.; Sigurdsson, Vigfús; et al.
Abstract: Introduction: The optimal time interval between diagnostic excision of a primary cutaneous melanoma and sentinel node (SN) biopsy is unknown. The current study sought to determine whether this interval influenced the SN-positivity rate, recurrence or survival. Methods: Data collected from 2004 to 2014 for a Dutch population-based cohort of patients with melanoma who underwent SN biopsy (SNB) within 100 days of initial diagnosis (n = 7660) and for a similarly specified cohort from a large Australian melanoma treatment centre (n = 3478) were analysed. Time to SNB was analysed continuously (in weeks) and categorically (per month). The effects of SNB timing on SN-positivity were assessed using multivariable logistic regression, and its effects on recurrence-free survival (RFS) and overall survival (OS) were assessed using Cox proportional hazard regression analyses. Advanced modelling using a multivariable Cox model with penalised splines for modelling the continuous effects of time to SNB on RFS and OS was also performed. Results: In neither the Dutch nor the Australian cohort was there a significant association between time to SNB and SN-positivity in either cohort, nor was there an impact of time to SNB on RFS or OS in either cohort. The spline-based HR curves for RFS and OS confirmed these findings. Conclusions: The time interval between diagnostic excision of a primary melanoma and SNB did not influence the SN-positivity rate or survival outcomes. This provides reassurance that neither early nor delayed definitive wide excision and SNB will adversely affect prognosis. Highlights: The optimal timing of sentinel node (SN) biopsy after melanoma diagnosis is unknown. This study examined the effects of timing on SN-positivity and survival. There was no significant association between time to SN biopsy and SN-positivity. There was no significant association between time to SN biopsy and survival.